The Impact of Social Pressure and Monetary Incentive on Cognitive Control - Ličen, Mina; Hartmann, Frank; Repovš, Grega; Slapničar, Sergeja (Frontiers in Psychology, 2016)
We compare the effects of two prominent organizational control mechanisms—social pressure and monetary incentive—on cognitive control. Cognitive control underlies the human ability to regulate thoughts and actions in the pursuit of behavioral goals. Previous studies show that monetary incentives can contribute to goal-oriented behavior by activating proactive control. There is, however, much less evidence of how social pressure affects cognitive control and task performance. In a within-subject experimental design, we tested 47 subjects performing the AX-CPT task to compare the activation of cognitive control modes under social pressure and monetary incentive beyond mere instructions to perform better. Our results indicate that instructing participants to improve their performance on its own leads to a significant shift from a reactive to a proactive control mode and that both social pressure and monetary incentive further enhance performance.